The determinants of bank capital in liquidity creation of banking sectors: evidence from Malaysia - Rashid, Siti Nurul Hazieqah (2019)
The study is carried out to investigate the determinants of bank capital and liquidity creation of banking sector in Malaysia. There are five bank specic determinants selected namely bank capital as the main independent variable and other variable that control variable is bank size, credit risk, and bank profitability. Top banks that have been chosen are namely AMBANK Group, Hong Leong Bank, CIMB Bank, RHB Bank, Public Bank and Maybank Berhad. The duration for this study are from 1999 until 2018 and the data is extract from annual report of commercial bank. Pooled OLS Model are carried out to investigate the finding from data. The results show there is two positive relationship and two negative relationship with liquidity creation of the banks.